The echinoid Parechinus angulosus and its association with other invertebrates - Robertson-Andersson, Deborah (Department of Biological Sciences, 2017)
Echinoids are recognized as important components of temperate kelp forests because of the impact that they have by grazing. The provision of shelter by some echinoid species for both juvenile conspecifics and for other species of echinoids has been widely documented. The behaviour is thought to be important in the survival of these species. The role of echinoids as protective "nurseries" for several types of marine animals has also been suggested. Adult echinoids are supported 1 - 2 cm above the substrate by the oral spines, this leaves a gap under the echinoid where other organisms can shelter. This paper examines firstly what types of organisms associate with the echinoid Parechinus angulosus and the degree to which they display tight relationships vs. chance associations. Secondly, it explores how much selectivity of the echinoids was involved when compared to other physical shelters and open substrate. This was done by comparing differences in the species associated with level, flat rocks covered with crustose corallines; the holdfasts of Ecklonia maxima; sand, and under echinoids. The study was done at four sites in False Bay, Cape Peninsula, South Africa. Samples were collected on each habitat type by placing a bottle over the substrate and scraping the sample into the bottle. The organisms in each sample were identified under a microscope and counted. The available habitat at each site was survey by divers swimming 6 am transects and noting the cover of a particular habitat falling under the tape measure. The total number of species and organisms for each site were compared using one-way and two-way ANOVA's on untransformed data. The availability of different habitat types at each site was compared, using one-way fixed-effects ANOVA. Results showed that there was no significant difference between habitat availability at the different sites. Results of the two-way ANOVA's comparing site and habitat for individual species showed that the amphipod Paramoera capensis only occurred in significant numbers at one echinoid site. The fact that 65 % of this species had a colour variation that matched the echinoid, implied that the amphipod gains protection from predators by being associated with subtidal echinoids. This relationship is not obligate as this amphipod was found in other habitats. The echinoid Parechinus angulosus appears to have a dual habitat preference with juveniles less than 1 O mm in diameter sheltering beneath adult conspecifics and juveniles greater than 1 o mm in diameter sheltering in kelp holdfasts. The amphipod Hyale grandicomis occurred in significant numbers associated with echinoids and had a habitat preference for echinoids, suggesting that it has an important relationship with subtidal echinoids. The amphipod is a known grazer of macroalgae and thus it is possible that the amphipod gets access to a food resource in the form of drift kelp, which is trapped by the echinoid. If this is the case then the amphipod would also be gaining protection from predators by being associated with the echinoid as the amount of time it is exposed while foraging is minimal.